Diagnostic potential of salivary MMP-9 to differentiate between periodontal health and disease in smokers and non-smokers - Tamarah Adil Mohammed Hussein - Omar Husham Ali ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The drawbacks of the traditional methods for detecting and managing periodontal disease motivated researchers to look for new ways to predict, diagnose, and monitor this condition. Using the biomarkers present in oral fluids could be a groundbreaking alternative to the manual probing/radiographic diagnosis. Several salivary biomarkers can accurately distinguish between periodontal health and disease. The aim of this study was to evaluate the diagnostic accuracy of salivary Matrix Metalloproteinase-9 (MMP-9) for differentiating healthy and diseased periodontal tissues in smokers and non-smokers. The study involved 175 participants who were classified into five equal groups: 1) healthy controls, 2) non-smoker gingivitis, 3) smoker gingivitis, 4) non-smoker periodontitis and 5) smoker periodontitis patients. Periodontal parameters including plaque index (PI), bleeding on probing (BOP), probing pocket depth (PPD), and clinical attachment level (CAL) were recorded for each patient. The salivary MMP-9 concentration was ascertained using an ELISA test. The diagnostic capabilities of MMP-9 were evaluated using the Receiver Operating Characteristic (ROC) curve and the Area Under the Curve (AUC). Salivary MMP-9 was significantly higher in patients with gingivitis and periodontitis compared to healthy individuals. The ROC analysis revealed that salivary MMP-9 had a high sensitivity and specificity to distinguish between periodontal health and both gingivitis and periodontitis regardless of whether the patient smoked or not. salivary MMP-9 demonstrated high sensitivity and specificity in distinguishing between healthy and diseased periodontal conditions. The level of accuracy of MMP-9 was also sufficient regardless of smoking status.